Sonic the Hedgehog 2 [videorecording (Blu-Ray)] - Casey, Patrick, 1978-; Miller, Josh; Whittington, John (Screenwriter); Marsden, James, 1973-; Sumpter, Tika; Rothwell, Natasha, 1980-; Pally, Adam, 1982-; Moore, Shemar, 1970-; Majdoub, Lee; Carrey, Jim, 1962- (Paramount, 2022)
Attempting to settle into his new life in Green Hills, Sonic finds himself with an excess of energy, time, and boredom as he longs to prove himself to be a true hero. He gets his chance when creatures from his own world begin showing up in search of an emerald with the power to destroy civilizations -- Dr. Robotnik has brought a powerful ally, Knuckles the Echidna, but a fox named Tails arrives to help Sonic stand in their way.